IMPROVING STUDENTS’ READING COMPREHENSION BY USING ALOUD READING ON THE FIFTH SEMESTER OF MIDWIFERY STUDENT AT STIK BINA HUSADA PALEMBANG - Arief Pamuji (Language and Education Journal, 2019)
The objective of this research was to find out whether or not there was an improving students’ reading comprehension by using aloud reading on the midwifery student at STIK Bina Husada Palembang. The sample of this research was taken by using purposive sampling technique with 70 midwifery students. The data were obtained by using pre and post reading test. To verify the hypotheses, the primary data were analyzed by using t test and regression analyses by means of Statistical Product and Service Solution (SPSS) version 21.00 computer program. Based on the data analysis, paired sample correlation in control group was 0,481 and experiment group was 0.822 at the significance level p< 0.05 in two tailed. It means that 82% aloud reading influece the improving students’ reading comrehension. And mean that the reading aloud technique in control group in post test was 64,60 and 84,51. It means that there was a significant improving on the students’ comprehension on the fifth semester of midwifery students at STIK Bina Husada Palembang